The lack of English oral proficiency among the Bidayuh students in rural secondary schools in Kuching and Samarahan divisions of Sarawak / Antel Set - Antel, Set (2009)
The purpose of this study is to find out the causes that lead to lack of English oral proficiency among the Bidayuh rural school students in Sarawak. The study also aims to find out how much exposure and opportunity Bidayuh students have to speak the English language, inside and outside the classrooms. One hundred form four Bidayuh students of SMK Taee, SMK Tebakang, SMK Dragon and SMK Siburan in Samarahan and Kuching Divisions of Sarawak are the samples of the study. 25 Bidayuh students were selected at random from each school. Form 4 Bidayuh students were selected as target group as they had spent their three years in lower secondary and this time is the most appropriate time to look into their oral proficiency level. Two English teachers from each school were also involved in this study. English teachers were selected as respondents as they had better insight understanding toward students' oral proficiency level. The data for this study were collected through two sets of questionnaire; Students and teachers as respondents. The first set of questionnaires was based on students' perspective while the other set was based on teachers' perspective. The selection of the four schools was done on the basis of their rural locality. The findings revealed that rural secondary school Bidayuh students in the two Divisions (Kuching and Samarahan) have a very low level of English proficiency due to certain reasons: poor socio-economic background, minimal exposure to English at home since childhood, preference for their mother tongue to English when conversing with their classmates even during English lessons and a lack of initiative to upgrade their oral skills by involving themselves in language activities or competition. On the other hand, English teachers did not take this problem (lack of English proficiency) seriously. Teachers tended to focus on students' performances in examination; drilled students with exam formats and techniques of answering questions. Besides that, teachers did not use English even during English lessons. Therefore, in most cases where students and teachers were concerned, 'Oral Proficiency' has been neglected. The results of the study indicate that the Bidayuh rural secondary schools students in Sarawak as well as their teachers do not take English oral proficiency problem seriously but focus on students' performance in written examination.